Board attributes, risk management and financial performance: Insights from Iraq - Abubakar, Ahmad Haruna; Ibrahim, Bashar Yousif; Zakaria, Nur Nashreen Binti; Kassim, Siti Fatimah Binti Mohd (goodwood publishing, 2023)
Purpose: This study examines how good corporate governance practices and the establishment of risk management committees reduce investors’ risks and improve performance. Research Methodology: Data stream and annual reports were used to acquire secondary data for all 21 banks listed on the Iraqi Stock Exchange between 2019 and 2021, totalling 63 firm-year observations. Data were analyzed using Stata version 15. Results: The data show that board size and independence have strong negative relationships with bank performance. The financial knowledge of the board and independence of the risk management committee had minor positive relationships with performance. Limitations: This study examines board size, independence, financial expertise, and the presence of a risk management committee. Other factors that may impact bank performance include the type of ownership structure, audit committee, and the application of additional financial performance indicators such as Tobin’s Q. Future research could expand to encompass these factors. Contribution: This study aims to provide valuable insights to the Iraqi government and regulators, aiding them in formulating new policies and deliberating on issues related to corporate governance concerning bank performance. It is well-established that both shareholders and companies rely on robust corporate governance mechanisms, especially as a means of augmenting bank value Novelty: The presence of a risk management committee reduces managers' discretion to engage in opportunistic behavior. This study educates regulators on the importance of firms having sound corporate governance and separate and active risk management committees to improve internal control.